Media Pembelajaran Monopoli Kebhinekaan Sebagai Penguatan Nasionalisme Di Sanggar Bimbingan Sentul Malaysia - Maharani, Deaningma; Mahardhani, Ardhana Januar; Cahyono, Hadi; Hudijono, Singkir; Subangun, Subangun; Asiyah, Siti; Indriastuti, Niken Reti; Mustikawati, Diyah Atiek; Ruhardi, Rudi (IAHN Gde Pudja Mataram, 2024)
Local Indonesian wisdom is a local culture that needs to be introduced to students at SB Sentul Malaysia as a means of strengthening feelings of love for the homeland and nationalism. The situation found at SB Sentul is that the Indonesian children there still have little knowledge of the local wisdom of the archipelago in Indonesia, so this service activity aims to introduce local wisdom of the archipelago through Monopoly Diversity learning media. The implementation method goes through four stages, namely the analysis, creation, implementation and evaluation stages. The results of this activity show that from the results of the evaluation given to students it is known that students' understanding of the local wisdom of this archipelago has increased so that it will increase the spirit of nationalism of students at SB Sentul..